Благословение/ Б. Плейн. Кентерберийская сказочка - Плейн Белва (Купидон, 1994)
Экземпляры: Армязьская библиотека (20200918) / Инвентарный номер: 9927 / Цена: / Авт.знак: П38 / ГРНТИ: 17.82 / ББК: 84(7США)